ANALISIS NILAI TAMBAH KACANG TANAH PADA USAHA KACANG SANGRAI â€œFANIAâ€ DI DESA KANONANG IV KECAMATAN KAWANGKOAN BARAT (Analysis of Peanut Added Value in the â€œFaniaâ€ Roased Bean Business in Kanonang IV Village Kawangkoan District) - Fandiko Hiskia Brilian Koampa; Rine Kaunang; Grace A. J. Rumagit (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to analyze the added value of the business of processing peanuts into roasted peanuts. The research was carried out for 2 months, from November to December 2021 at the â€œFaniaâ€ Roasted Bean business in Kanonang IV Village, West Kawangkoan District, Minahasa Regency, North Sulawesi. Data collection using a survey method. Type of data used was primary data obtained through direct interviews with roasted peanut business owners "Fania" and employees as well as direct observation at the research site. The results showed that the added value of the business of processing peanuts into roasted peanuts was IDR 1,701 per liter.